Reflux of Endoplasmic Reticulum proteins to the cytosol inactivates tumor suppressors. (12th March 2021) - Sicari, Daria; Centonze, Federica G; Pineau, Raphael; Le Reste, Pierre‐Jean; Negroni, Luc; Chat, Sophie; Mohtar, M Aiman; Thomas, Daniel; Gillet, Reynald; Hupp, Ted; Chevet, Eric; Igbaria, Aeid
Abstract: In the past decades, many studies reported the presence of endoplasmic reticulum (ER)‐resident proteins in the cytosol. However, the mechanisms by which these proteins relocate and whether they exert cytosolic functions remain unknown. We find that a subset of ER luminal proteins accumulates in the cytosol of glioblastoma cells isolated from mouse and human tumors. In cultured cells, ER protein reflux to the cytosol occurs upon ER proteostasis perturbation. Using the ER luminal protein anterior gradient 2 (AGR2) as a proof of concept, we tested whether the refluxed proteins gain new functions in the cytosol. We find that refluxed, cytosolic AGR2 binds and inhibits the tumor suppressor p53. These data suggest that ER reflux constitutes an ER surveillance mechanism to relieve the ER from its contents upon stress, providing a selective advantage to tumor cells through gain‐of‐cytosolic functions—a phenomenon we name ER to Cytosol Signaling (ERCYS). Synopsis: Endoplasmic Reticulum (ER) stress in cancer cells causes a subset of ER proteins to escape to the cytosol where they bind and inhibit key signaling pathways to increase cancer cell fitness. ER stress mediated protein reflux is a conserved ER surveillance mechanism from yeast to mammals that plays a physiological role to relieve the ER from its contents upon ER stress. ER refluxed proteins gain new functions once they are in the cytosol. The refluxed PDI‐like protein AGR2 inhibits p53 signaling by binding and inhibiting p53 protein Abstract : Endoplasmic Reticulum (ER) stress in cancer cells causes a subset of ER proteins to escape to the cytosol where they bind and inhibit key signaling pathways to increase cancer cell fitness.